REFORM, ORGANISATION AND CONSOLIDATION OF THE ROMANIAN BANKING SYSTEM - ION Gr. IONESCU (Annals of the University of Petrosani: Economics)
Banking system, making the economic environment and the resources it provides, the subsystem consists of macro economic and social. He is in continuous interaction with the economic environment, which takes "input" in various forms - human, financial, information they process into "outputs" - products and banking services, financial derivatives used in banking, financial and banking information, etc. In other words, and the banking system is now an open system. What is specific to open systems, and hence the banking system is that it regulates activity by reverse connection (feed back), so they are capable of self.